(untitled) (Journal of Applied Oral Science, 2009)
The light-curing technique is relevant to reduce the degree of polymerization shrinkage, improving clinical and esthetic success of composite resin restorations. OBJECTIVE: To evaluate in vitro the effect of four light-curing techniques on depth of cure of a composite resin. MATERIAL AND METHODS: Ten specimens of a composite resin were made in cylindrical cavities prepared in PVC plates (3.0 X 7.0 mm) for each light-curing technique. Four photoactivation methods were investigated: stepped, ramped, pulse-delay and traditional. Specimens were longitudinally sectioned and polished for microhardness measurements (kg/mm²), which were made at 0.1, 1.0, 2.0 and 4.0 mm from the irradiated surface. Data were subjected to ANOVA and Tukey's test. RESULTS: The effect of factors studied (curing method and distance from the surface) and the interaction of these factors was statistically significant (p